MUCOSA JEJUNAL EM PACIENTES COM DESNUTRICAO PROTEICA, ANEMIA E PARASITOSES - Vannucchi, H.; De Franco, M. F.; Campana, A. O. (My University, 1974)
The data on 19 adult patients with anemia and malnutrition are presented. A scoring system was used in order to classify the degree of protein calorie malnutrition. The patients were also grouped according to the serum hemoglobin level. The authors investigated the parasitic infection and the microscopic appearances of the jejunum specimens were also studied. The data suggested an association between the severity of protein calorie malnutrition and the intensity of mucosal abnormalities. The infestation with Strongyloides seems to be associated with severe mucosal changes; this seems not to be the case as far as the hookworm infection is concerned. The degree of anemia does not seem to have a definite relationship with the severity of disturbed mucosal patterns.
The jejunal mucosa in patients with malnutrition, anemia and parasitic infection